No effect of monthly supplementation with 12000 IU, 24000 IU or 48000 IU vitamin D3 for one year on muscle function: The vitamin D in older people study. Issue 190 (June 2019) - Ranathunga, R.M.T.K.; Hill, T.R.; Mathers, J.C.; Francis, R.M.; Prentice, A.; Schoenmakers, I.; Aspray, T.J.; ,
Highlights: The effect of vitamin D on muscle strength, assessed by Grip Strength (GS) and function by Timed-up and Go test (TUG), were assessed in older people. We found that a plasma 25-hydroxyvitamin D <25 nmol/L at baseline was associated with lower GS. There was no dose effect on GS or TUG, comparing 12000IU, 24000IU or 48000IU of vitamin D per month for one year in people aged 70+ years. However, in the absence of a placebo group, we have cannot exclude a possible benefit of all three doses. Abstract: Vitamin D plays a role in muscle function through genomic and non-genomic processes. The objective of this RCT was to determine the effect of monthly supplemental vitamin D3 onmuscle function in 70+ years old adults. Participants (n = 379) were randomized to receive, 12, 000 IU, 24, 000 IU or 48, 000 IU of vitamin D3 monthly for 12 months. Standardized Hand Grip Strength (GS) and Timed-Up and Go (TUG) were measured before and after vitamin D3 supplementation. Fasting total plasma 25 hydroxyvitamin D (25OHD) and Parathyroid Hormone (PTH) concentrations were measured by Liquid Chromatography Tandem Mass Spectrometry (LC-MSMS) and immunoassay, respectively. Baseline plasma 25OHD concentrations were 41.3 (SD 19.9), 39.5 (SD 20.6), 38.9 (SD 19.7) nmol/L; GS values were 28.5 (SD 13.4), 28.8 (SD 13.0) and 28.1 (SD 12.1) kg and TUG test values were 10.8 (SD 2.5), 11.6 (SD 2.9) and 11.9 (SD 3.6) s for the 12, 000 IU, 24, 000 IU and 48, 000 IU dose groups, respectively. Baseline plasma 25OHD concentration < 25 nmol/L was associated with lower GS ( P = 0.003). Post-interventional plasma 25OHD concentrations increased to 55.9 (SD 15.6), 64.6 (SD15.3) and 79.0 (SD 15.1) nmol/L in the 12, 000 IU, 24, 000 IU and 48, 000 IU dose groups, respectively and there was a significant dose-related response in post-interventional plasma 25OHD concentration (p<0.0001). Post-interventional GS values were 24.1 (SD 10.1), 26.2 (SD10.6) and 25.7 (SD 9.4) kg and TUG test values were 11.5 (SD 2.6), 12.0 (SD 3.7) and 11.9 (SD 3.2) s for 12, 000 IU, 24, 000 IU and 48, 000 IU dose groups, respectively. The change (Δ) in GS and TUG from pre to post-intervention was not different between treatment groups before and after the adjustment for confounders, suggesting no effect of the intervention. Plasma 25OHD concentration was not associated with GS and TUG test after supplementation. In conclusion, plasma 25OHD concentration < 25 nmol/L was associated with lower GS at baseline. However, monthly vitamin D3 supplementation with 12, 000 IU, 24, 000 IU and 48, 000 IU, for 12 months had no effect on muscle function in older adults aged 70+ years. Trial Registration : EudraCT 2011-004890-10 and ISRCTN35648481.